Analysis of accelerometer-derived interpersonal spatial proximities: A calibration, simulation, and validation study. Issue 3 (3rd July 2018) - McCullough, Aston K.; Keller, Bryan S.; Qiu, Shumin; Garber, Carol Ewing
ABSTRACT: The purpose of this study was to estimate distances from accelerometer-derived Bluetooth signals as a measure of interpersonal spatial proximity. Accelerometer-derived proximity data were collected indoors and outdoors over a 10m range to calibrate simulation models. Proximity data were simulated over 20m (indoor) and 50m (outdoor) ranges. Competing statistical and machine learning models were used to predict simulated distances; the Root-Mean-Square-Error (RMSE) was calculated. Simulation estimates were validated under conditions wherein a single beacon-receiver (SBR) and multiple beacons-receivers (MBR) collected proximity data indoors and outdoors within a ≤10m range. Simulation data showed that a Random Forest (RF) model performed optimally. The validated RF RMSE was ≤2.7 for SBR, and ≥90% of predicted distances were accurately classified as ≤10m. For MBR, ≥67% of predicted distances were accurately classified as ≤10m. Simulation and validation data suggest that distances can be estimated from accelerometer-derived proximity data within a 20m range using a SBR.